Ion distribution functions in magnetotail reconnection: global hybrid-Vlasov simulation results - Runov Andrei; Grandin Maxime; Palmroth Minna; Battarbee Markus; Ganse Urs; Hietala Heli; Hoilijoki Sanni; Kilpua Emilia; Pfau-Kempf Yann; Toledo-Redondo Sergio; Turc Lucile; Turner Drew (COPERNICUS GESELLSCHAFT MBH, 2022)
We present results of noon-midnight meridional plane global hybrid-Vlasov simulations of the magnetotail ion dynamics under a steady southward interplanetary magnetic field using the Vlasiator model. The simulation results show magnetotail reconnection and formation of earthward and tailward fast plasma outflows. The hybrid-Vlasov approach allows us to study ion velocity distribution functions (VDFs) that are self-consistently formed during the magnetotail evolution. We examine the VDFs collected by virtual detectors placed along the equatorial magnetotail within earthward and tailward outflows and around the quasi-steady X line formed in the magnetotail at X approximate to -14 RE. This allows us to follow the evolution of VDFs during earthward and tailward motion of reconnected flux tubes as well as study signatures of unmagnetized ion motion in the weak magnetic field near the X line. The VDFs indicate actions of Fermi-type and betatron acceleration mechanisms, ion acceleration by the reconnection electric field, and Speiser-type motion of ions near the X line. The simulated VDFs are compared and show good agreement with VDFs observed in the magnetotail by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) and Acceleration, Reconnection, Turbulence and Electrodynamics of Moon's Interaction with the Sun (ARTEMIS) spacecraft. We find that the VDFs become more gyrotropic but retain transverse anisotropy and counterstreaming ion beams when being convected earthward. The presented global hybrid-Vlasov simulation results are valuable for understanding physical processes of ion acceleration during magnetotail reconnection, interpretation of in situ observations, and for future mission development by setting requirements on pitch angle and energy resolution of upcoming instruments.